Target of Verbal Abuse in Comments on Instagram Account @Gibran_Rakabuming: an Educational Perspectives - rahim, rahmatia; Setiawan, Teguh (Paedagogia: Jurnal Pendidikan, 2024)
This study aims to describe the target aspects of verbal violence in comments on the Instagram account @gibran_rakabuming in educational perspective. Using a descriptive qualitative approach, the research applies pragmatic matching analysis techniques to delve deeper into the forms of verbal violence and the identity aspects targeted by these attacks, including ethnicity, religion, race, inter-group relations (SARA), gender, disability, and sexual orientation. The findings indicate that verbal violence is most often directed at inter-group aspects, reflecting high tensions between social groups in the digital space, particularly in the political context. Additionally, aspects of religion and race frequently become targets, further complicating the polarization on social media. This study reveals the role of social media as an arena where verbal violence thrives and indirectly reinforces social segregation, especially on sensitive identity issues. In conclusion, these findings demonstrate that comments on social media serve not only as a space for expression but also as a venue for intense verbal conflicts related to individual and group identities.